On Interval-Valued Pseudolinear Functions and Interval-Valued Pseudolinear Optimization Problems. (2nd June 2015) - Zhang, Jianke; Zheng, Qinghua; Zhou, Chang; Ma, Xiaojue; Li, Lifeng
Abstract : Some basic characterizations of an interval-valued pseudolinear function are derived. By means of the properties of interval-valued pseudolinearity, a class of interval-valued pseudolinear programs is considered, and the solution set of the interval-valued pseudolinear optimization problem is characterized.